Monitoring a CuO gas sensor at work: an advanced in situ X-ray absorption spectroscopy study - Volanti, D. P. [UNESP]; Felix, A. A.; Suman, P. H.; Longo, E.; Varela, J. A.; Orlandi, M. O. (Royal Society of Chemistry, 2015)
X-ray absorption near edge structure (XANES) and electrical measurements were used to elucidate the local structure and electronic changes of copper(II) oxide (CuO) nanostructures under working conditions. For this purpose, a sample holder layout was developed enabling the simultaneous analysis of the spectroscopic and electrical properties of the sensor material under identical operating conditions. The influence of different carrier gases (e.g., air and N2) on the CuO nanostructures behavior under reducing conditions (H2 gas) was studied to analyze how a particular gas atmosphere can modify the oxidation state of the sensor material in real time.